Implementasi Peraturan Bupati Purwakarta No. 69 Tahun 2015 Tentang Pendidikan Berkarakter - Pikri, faizal; Abubakar, Rodlial Ramdhan Tackbir; Adawiyah, Nurmilah (Publica: Jurnal Pemikiran Administrasi Negara, 2019)
Education is one of the basic things tha must be obtaned by citizen in every country. This research is motivated by there are complaints from parents who do not have time to prepare food for their children who attend school too late in the morning. However, there are students or teachers who come late and don?t break the rules. The purpose of this research is to analyze the implementation of regent regulations related to school hours rules. The theory used in this research is the theory of Edward III which includes communication, resources, disposition, and bureaucratic structure. The research method use is descriptive research reluctant to use qualitative approach. The data collection technique is direct observation, in-depth interview, library study, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The result of the study show that the policy of school hours at 06.00 is not appropriate to be implemented. Therefore, some improvements are needed regarding the policy regulations.